Diversity in the Altai Republic Diversity of Mammal Communities and Its Correlation with Stability of Natural Complexes of the South Eastern Altai - MALKOV, Peter Yu.; KARANIN, Andrey V.; ZHURAVLEVA, Olga V.; SUKHOVA, Maria G. (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019, 2019)
Studies of ecology and fauna are still important for studies of animal communities, important components of ecosystems of various levels. The article analyses the spatial distribution and diversity of communities and individual mammal species in the South Eastern Altai. The characteristics of land habitats and the integral ecosystem stability factor are compared to assess the consistency of their territorial changes. The contribution of various natural complexes to the maintenance and preservation of mammal diversity in the South-Eastern Altai is shown. It has been shown that the highest diversity of mammal species is commonly found in landscapes with medium classes of the stability range. It has been shown that the prerequisite for the sustainable development of the region is the preservation and restoration of natural complexes both with relatively low environmental stability and increased level of diversity of biological components.